A Study on Pattern of Spine Trauma in Patients Presented to Khyber Teaching Hospital, Peshawar (Journal of Pakistan Orthopaedic Association, 2024)
Objective: This study was conducted to assess the pattern of spine trauma in patients presenting to Khyber teaching hospital in terms of level of injury, etiology, fracture type, and neurologic deficit.Methods: This cross sectional study was performed at orthopedic surgery unit, Khyber teaching hospital, Peshawar. Patients presenting with spinal; cord injuries were included. Etiology, level of injury, types of fracture and neurologic deficit was recorded and assessed. Chi square test was performed for the assessment of association.Results: The mean age of the patients was 33.28±9.63 years. There were 88 (69.3%) males and 39 (30.7%) females. Fall from height (50.4%) was the most prevalent etiology followed by RTA (30.7%). Thoracolumbar spine injury (49.6%) was the most prevalent level of spinal injury followed by cervical spine injury (29.9%). Majority patients had type A fracture 43.3%), type B (37%) was second leading fracture. Neurologic deficit was seen in 54.3% patients.Conclusion: Fall from height is the most cause of spinal traumas in our country and road traffic accidents are the second leading cause. Thoracolumbar spine injury was the major presentation of the spinal injury location and type A was the most common type of fracture. Majority of the patients had neurologic deficit.